Biomechanical determinants of elite high jump performance in Egypt: Part 1 - analysis of kinematic variables and performance - Atta, I. I.; Bursais, A. K.; Alibrahim, M. S.; Al-Nuaim, A. (Journal of Physical Education and Sport, 2024)
This study extends previous research by examining the biomechanical factors influencing the performance of elite high jumpers during a 2020 competition. The study involved 16 athletes (mean height: 1.98 m, mean weight: 87 kg, mean age: 30 years). Biomechanical analysis was performed using six GoPro Hero 6 cameras set at 120 frames per second, capturing 48 jump attempts (three attempts per athlete). The three-dimensional biomechanical analysis program Skillspector was used to measure biomechanical variables, temporal analysis parameters, and moment variables, including the moments of takeoff initiation, maximum knee flexion of the takeoff leg, takeoff completion, flight initiation, and maximum body height during flight. Results. There were inverse relationships between height achieved and the braking time and the angle of the knee joint of the free leg at the takeoff, and direct relationships between height achieved and the vertical momentum and vertical kinetic energy of the body's center of gravity. Conclusions. Increasing the vertical kinetic energy at the beginning of takeoff would increase the lift force.